2019
DOI: 10.1111/srt.12747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors triggering sensitive scalp in Korean adult women

Abstract: Background The scalp care market is growing rapidly and research into the factors associated with sensitive scalp is performed in many countries. However, to the best of our knowledge, no previous study has examined the factors triggering sensitive scalp in Korean women. Thus, the aim of our study was to establish objective standards for sensitive scalp, investigate factors that trigger this condition, and determine the ratio of sensitive scalp in Korean women. Methods A total of 125 Korean adult women partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In the 27 patients with scalp dermatosis, 59% of the subjects had a "very sensitive" or "sensitive" scalp. In a recent study in which subjects were asked, "Do you have sensitive scalp?, " 56% had a positive answer (12). Other studies reported frequencies of 32% (11), 36% (12), or 44.2% (6), with a higher frequency in women.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the 27 patients with scalp dermatosis, 59% of the subjects had a "very sensitive" or "sensitive" scalp. In a recent study in which subjects were asked, "Do you have sensitive scalp?, " 56% had a positive answer (12). Other studies reported frequencies of 32% (11), 36% (12), or 44.2% (6), with a higher frequency in women.…”
Section: Discussionmentioning
confidence: 92%
“…In a study including 125 Korean adult women, the major triggering factor cited was hair care products, as it was cited as a triggering factor in 65.6% of subjects in the group with sensitive scalp (12). There are several types of cosmetics care products for the hair: the hair conditioners, the masks, the oils, the lotions, the serums.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the purpose of our study is to set objective criteria for sensitive scalp, investigate the factors that cause this condition, and determine the percentage of sensitive scalp in Korean women. This study can help understand the sensitive scalp characteristics of Korean women and identify the factors that cause sensitive scalp 28 . They investigated the correlation between the degree of temporal hair loss and other areas of scalp hair loss in Korean female type hair loss patients.…”
Section: Resultsmentioning
confidence: 99%
“…This study can help understand the sensitive scalp characteristics of Korean women and identify the factors that cause sensitive scalp. 28 They investigated the correlation between the degree of temporal hair loss and other areas of scalp hair loss in Korean female type hair loss patients. A total of 109 women with female-type hair loss were enrolled in this retrospective analysis.…”
Section: Several Main Causes and Types Of Scalp And Hair Lossmentioning
confidence: 99%